No. 33 -- Totem Poles at Howkan (Manuscripts, Archives, and Special Collections, Washington State University Libraries: https://libraries.wsu.edu/masc, 1898)
1 Lantern Slide: b&w; 10 x 8 cm. Howkan is an Tlingit village on the southeast coast of Alaska, known as the "Alaskan Panhandle." Reproduction photograph acquired by Mart Albert Howard for instructional/educational purposes.